Long‐Term Risk Perceptions of Women With Ductal Carcinoma In Situ. (8th April 2013) - Ruddy, Kathryn J.; Meyer, Meghan E.; Giobbie‐Hurder, Anita; Emmons, Karen M.; Weeks, Jane C.; Winer, Eric P.; Partridge, Ann H.
Abstract : Learning Objectives: Identify predictors of excessive risk perception in women with a distant history of DCIS. Explain the importance of educating women with a history of DCIS about reasonable assessments of their risk for future breast cancer. Introduction: Previous research has demonstrated that many women with ductal carcinoma in situ (DCIS) overestimate their risk for future breast cancer at the time of diagnosis and soon thereafter. This study aims to evaluate risk perceptions after 5 years. Patients and Methods: In a longitudinal cohort study, we mailed long‐term follow‐up surveys to 315 women who had previously responded to a survey 18 months after they were diagnosed with DCIS, excluding those who had experienced recurrence and those not treated at our institution. We evaluated risk perceptions with items used previously in the cohort. Results: One hundred ninety‐three women (61%) responded. The median time since diagnosis was 5.9 years. We excluded 12 because of recurrence. Of the 181 remaining, 32% perceived at least a moderate 5‐year risk for developing DCIS again, 43% perceived at least a moderate lifetime risk for developing DCIS again, 27% perceived at least a moderate 5‐year risk for invasive breast cancer, 38% perceived at least a moderate lifetime risk for invasive breast cancer, and 24% perceived at least a moderate risk for DCIS spreading to other body parts. In a multivariate model, worse financial status and higher perceived risk in the previous survey were the only predictors of at least a moderate perception of risk for DCIS spreading. Conclusion: Women with a history of DCIS continue to harbor inaccurate perceptions of their risk for future breast cancer events even 5 years after diagnosis. Abstract : Recurrence risk perceptions after 5 years were evaluated in women with a history of ductal carcinoma in situ. Many women were found to harbor inaccurate perceptions of their risk for future breast cancer events even 5 years after diagnosis.